Enduring Equity Questions: A Sequence Analysis of Citations in Response to Racial Inequity via the Individuals with Disabilities Education Act. (June 2023) - Kramarczuk Voulgarides, Catherine; Aylward, Alexandra
In this article, we document patterns of local education agency (LEA) disproportionality citations within one U.S. state spanning an 8-year time period immediately following the 2004 reauthorization of the Individuals with Disabilities Education Act (IDEA) to understand the following: (a) how patterns of disproportionality citations manifest over time in suburban locales, and (b) how often LEAs experience and subsequently are able to successfully address a citation for racial inequity in special education outcomes. We descriptively investigated sequence patterns across suburban locales within one state—New York State (NYS), which serves as a representative case for our analysis. We focus on suburban locales because prior research has documented that a school district's location (e.g., suburban) relates to the time frame within which a school district was able to address a disproportionality citation. In addition, locale-specific characteristics such as segregation in schools and communities and sociodemographic conditions influence the occurrence of racial disproportionality. Our primary questions driving the descriptive inquiry were as follows: How does variation in sequence patterns for IDEA disproportionality citations manifest within and between suburban locales in NYS? What are the policy implications of these patterns? We conclude with specific recommendations for improving IDEA racial equity policy.